Directed self-assembly of viologen-based 2D semiconductors with intrinsic UV–SWIR photoresponse after photo/thermo activation - Xiao-Qing Yu (Nature Portfolio, 2020)
Developing new materials with broadband photoresponse is highly desirable for realizing commercial photodetectors with extended detection ranges. Here, the authors report a cyanide-bridged layer-directed intercalation approach to design viologen compounds with enhanced broadband photoresponse.